2021
DOI: 10.18280/rcma.310102
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Lattice Strain in Lanthanum Hexa Aluminate Nanoparticles Using X-Ray Peak Profile Analysis

Abstract: This work confers to the preparation of Lanthanum Hexa Aluminate (LHA) nanoparticles by chemical precipitation and filtration technique followed by characterization studies conducted through X-ray peak profile analysis (XPPA) and Field Emission Scanning Electron Microscopy (FESEM) supported by Energy Dispersive Spectroscopy (EDS). From the X-ray diffraction (XRD) analysis, it has been observed that the prepared powder has hexagonal crystal structure. Further, Scherrer Method (S-M), modified Williamson–Hall (W-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The gradient of the linear fit indicates the strain, which is 3 74 10 % − ⋅ . The model aligns well with the experimental points, indicating the homogeneity of the structure [10], [11]. The investigation of the structure using Raman spectroscopy was conducted on the Solver Spectrum 600/600 spectrometer.…”
Section: Fig 3 Xrd Pattern Of Microcrystalline Pbs Thin Filmssupporting
confidence: 72%
“…The gradient of the linear fit indicates the strain, which is 3 74 10 % − ⋅ . The model aligns well with the experimental points, indicating the homogeneity of the structure [10], [11]. The investigation of the structure using Raman spectroscopy was conducted on the Solver Spectrum 600/600 spectrometer.…”
Section: Fig 3 Xrd Pattern Of Microcrystalline Pbs Thin Filmssupporting
confidence: 72%
“…Table 1 depicts the basic properties of materials used. LHA nanoparticles are synthesized using the stoichiometric reactions described by Yellapragada et al [23] in their previous work.…”
Section: Methodsmentioning
confidence: 99%
“…Majority of the prepared powders consists of aluminum and lanthanum peaks which indicate the process is prepared well. Sai et.al [28] in their previous works reported that prepared alumina lanthanum hexa-aluminate ceramic powders and crystallite size determination using peak analysis and reported that the youngs modulus is 298 Gpa and it is selected as a reinforcement. Sameer et.al reported that among various magnesium alloys AZ91E has emerged as best material in view of automotive applications [29].…”
Section: Methodsmentioning
confidence: 99%